Tetraethyl Vinylidenebisphosphonate: A Versatile Synthon for the Preparation of Bisphosphonates - Rodriguez, Juan B. (Synthesis, 2014)
Tetraethyl vinylidenebisphosphonate is a versatile synthetic intermediate that allows access to a variety of highly functionalized compounds bearing the bisphosphonic moiety. As an electron-deficient alkene, this compound is able to undergo conjugate addition with a variety of reagents including strong nucleophiles, such as organometallic reagents and enolates, as well as very mild nucleophiles, such as amines, mercaptans and alcohols. The title compound also possesses the ability to behave as a dipolarophile or dienophile in 1,3-dipolar cycloadditions or Diels–Alder reactions, giving rise to five- or six-membered rings containing the bisphosphonic unit. In summary, tetraethyl vinylidenebisphosphonate is a very useful synthon to have at hand for straightforward syntheses of bisphosphonate derivatives of diverse structures. This bisphosphonate moiety has proven to be very important to impart important pharmacological action.1 Introduction2 General Reactivity3 Michael Addition Reactions3.1 Reaction with Organometallic Reagents3.2 Reaction with Mercaptans and Amines3.3 Reaction with Phosphorus-Containing Nucleophiles3.4 Epoxidation, Loss of a Phosphonate Unit and Rearrangement Reactions3.5 Michael Reactions with Enolates4. Cycloaddition Reactions4.1 Diels–Alder Reactions4.2 1,3-Dipolar Cycloadditions4.2.1 Reaction with Diazo Compounds4.2.2 Reaction with Nitrones4.2.3 Reaction with Nitrile Oxides4.2.4 Grigg Azomethine Ylide Cyclizations4.2.5 Reaction with Azides5 Concluding Remarks
Keywords: bisphosphonates; tetraethyl vinylidene bisphosphonate; Michael additions; 1,3-dipolar cycloadditions